Analysis of Entertainment Content and Informative Content on Consumer Perceptions of Products - Yahya Muhaimin (Universitas 17 Agustus 1945 Semarang, 2025)
This study analyzes how informational videos and entertainment videos affect buyers' interest in buying an item. This study uses secondary data by analyzing the latest scientific articles by producing the results of the analysis of this study that informational videos and entertainment videos affect consumers' interest in buying products. With the presence of informational videos about the products offered and entertainment videos that offer products attract consumers' attention to buy products.